Forest Diversity and Management - Hawksworth, David L.; Bull, Alan T. (Topics in Biodiversity and Conservation, 2006)
Natural forests with thousands of years of ecological continuity are unrivalled as the treasure store of terrestrial biodiversity on Earth. And while there is currently no fully comprehensive inventory of the biota associated with any given forest, it is reasonable to assume that in conserving natural forests we can conserve the myriads of unnamed bacteria, fungi, insects, mites and nematodes that forests support. Drawing on diverse research from biodiversity experts around the world, this collection of papers reflects the diversity of forest types and forest issues that concern forest scientists globally. Forest types considered vary from savannah and tropical rainforests to the ancient oak forests of Poland; issues explored include the effects of logging, management practices, forest dynamics and climate change on forest structure and biodiversity. Given the range of topics covered, this book should be of particular interest to those involved in teaching forest conservation and management, as well as to researchers requiring an overview of current work in forest diversity, conservation and sustainable management. Reprinted from Biodiversity and Conservation 15:4 (2006). .